A review on microstructures and properties of high entropy alloys manufactured by selective laser melting. (20th July 2020) - Zhang, Chen; Zhu, Junkai; Zheng, Huai; Li, Hui; Liu, Sheng; Cheng, Gary J
Abstract: High entropy alloys (HEAs) with multi-component solid solution microstructures have the potential for large-scale industrial applications due to their excellent mechanical and functional properties. However, the mechanical properties of HEAs limit the selection of processing technologies. Additive manufacturing technology possesses strong processing adaptability, making itthe best candidate method to overcome this issue. This comprehensive review examines the current state of selective laser melting (SLM) of HEAs. Introducing SLM to HEAs processing is motivated by its high quality for dimensional accuracy, geometric complexity, surface roughness, and microstructure. This review focuses on analyzing the current developments and challenges in SLM of HEAs, including defects, microstructures, and properties, as well as strengthing prediction models of fabricated HEAs. This review also offers directions for future studies to address existing challenges and promote technological advancement.